Rostovtzeﬀ and Italy: A Long History - Marcone, Arnaldo (Hyperboreus, 2021)
In recent years, we have all become much more aware of Rostovtzeﬀ’s profound roots in early 20th-century European culture, of his speciﬁcally Russian traits as a scholar and, therefore, of what his mature historiography owes to the intertwining of these two components. Italy plays a major role in this context. To get an idea of the importance of Rostovtzeﬀ for De Sanctis’ school, we only need to glance at some of Momigliano’s early writings, in which the name of the Russian historian frequently appears.